Adsorption of Malachite Green Oxalate Dye by CuCo2O4/MgO Spinel Oxide Nanocomposite - Tariq Hussein Mgheer; Ali Abdulraheem Kadhim; Zainab Abdalameer Hussein; Zaid Kaheel Kadhim; Muneer Abdul Aly Al-Da’amy; Abbas Jassim Atiyah; Salih Hadi Kadhim; Suma Jaafar Abbas (Indonesian Journal of Chemistry, 2023)
The current study involves a synthesis of a composite of copper oxide and cobalt oxide as a spinel oxide load over magnesium oxide. This synthesis of nanocomposite material was from nitrate salts of the corresponding metals by co-precipitation method, while it was investigated by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction techniques (XRD), field emission scanning electron microscopy (FESEM), atomic force microscopy (AFM), and the activity of these materials was estimated by appreciated adsorption of malachite green oxalate (MGO) dye from its aqueous solution. Adsorption isotherm was investigated using both Freundlich and Langmuir adsorption isotherms. While the results of the spectrophotometric studies showed that the composition of synthesized supported oxides at 450 °C was spinel type with nanoparticle size, and the optimum removal efficiency was around 98% for the adsorption of MGO dye over spinel nanocomposite surface achieved by using a dye concentration of 5 ppm, a mass of adsorbent surface of 5 mg, in terms of the adsorption model's isotherms the obtained results showed that the removal of MGO dye by the surface of this material was more fitted with the Freundlich models' adsorption.